THE TAXONOMIC POSITION OF PAPUODENDRON C.T. WHITE AS ELUCIDATED BY ANATOMICAL CHARACTERS - Heel, W. A. van (Research Center for Biology, 1972)
When, in 1946, White described Papuodendron lepidotum from New Guinea, he apparently hesitated to incorporate this species in the Bombacaceae.